IMPLEMENTING THE MANDALA CONCEPT IN INTERSECTION LANDMARK PLANNING FOR SUSTAINABLE CITY DEVELOPMENT - Hadi, Cipta (JMARS: Jurnal Mosaik Arsitektur, 2025)
A monument has become a stereotype for a landmark design at a road intersection in most cities in Indonesia. However, that stereotype only possesses symbolic value, overlooking other values such as spatiality and sustainability. This study proposes an alternative approach to designing a landmark at a road intersection. Mandala, as local wisdom, becomes a basic principle that later develops into the general concept of landmark design. Through literature studies of landmarks and spatial experience of architecture, and also supported by design experiments through case studies, this study suggests the Mandala concept as one of the best solutions for the landmark at a road intersection design, which offers varied and explorative designs. By the Mandala design concept, a landmark design at a road intersection not only possesses symbolic value but also environmental and better spatial experience values.